Beyond the Research–Practice Gap: The Development of an Academic Collaborative Centre for Child and Family Social Work. (16th November 2017) - Steens, Roos; Van Regenmortel, Tine; Hermans, Koen
Abstract: The gap between research and practice has been a long-standing challenge in social work (e.g. Richmond, 1917 ; Rubin, 2014 ). Partnership structures between research facilities and social care organisations are seen as a possible way forward, but knowledge on how such partnerships can be successfully elaborated and implemented in local social work practices is scarce. In this article, we elaborate on our experiences in building an academic collaborative centre (ACC): a long-term partnership between a social service organisation and a university (see also ACCs for public health in the Netherlands, e.g. Garretsen et al., 2007 ; Molleman and Fransen, 2012 ; Jansen et al., 2015 ). Starting from the conceptual framework of Thompson et al. (2009), we open up the black box of our collaboration project and give insight into what turned out to be a long and messy but also a very rich and insightful process. We conclude by identifying three important aspects to implementing a research–practice partnership in local social work practice: (i) informal contacts between the different stakeholders and knowledge brokering, (ii) collaborative research projects and (iii) a general framework of mutuality and agreement in which differences can safely exist and negation can take place.